Influence of Herbicide Combinations and Sequential Applications on Windmillgrass (Chloris verticillata) Control - Nicholas Mitchell; Jared Hoyle (Kansas Agricultural Experiment Station Research Reports, 2019)
Windmillgrass (Chloris verticillataNutt.) populations commonly infest turfgrass systems in the midwest, which result in aesthetically unacceptable turfgrass stands. Pylex (topramezone) and Acclaim Extra (fenoxaprop) have resulted in fair control of windmillgrass with single applications. For adequate control of windmillgrass, a sequential application of Tenacity (mesotrione), three weeks after the initial application, is recommended. Additionally, studies have shown the addition of triclopyr to HPPD inhibitor herbicides increases windmillgrass control in a controlled environment. Field experiments were initiated in 2018, at the Kansas State University Rocky Ford Turfgrass Research Center in Manhattan, KS, to determine the influence of herbicide combinations with the addition of triclopyr and sequential applications on windmillgrass control.
Keywords: windmillgrass; weed control; herbicide combination; sequential applications